2018
DOI: 10.1016/j.tecto.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Uplift history of a transform continental margin revealed by the stratigraphic record: The case of the Agulhas transform margin along the Southern African Plateau

Abstract: The south and southeast coast of southern Africa (from 28°S to 33°S) forms a highelevated transform passive margin bounded to the east by the Agulhas-Falkland Fracture Zone (AFFZ). We analysed the stratigraphic record of the Outeniqua and Durban (Thekwini) Basins, located on the African side of the AFFZ, to determine the evolution of these margins from the rifting stage to present-day. The goal was to reconstruct the strike-slip evolution of the Agulhas Margin and the uplift of the inland high-elevation South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 100 publications
(119 reference statements)
2
51
0
Order By: Relevance
“…These were initiated at ~23 Ma, most likely due to an uplift event of the North-eastern part of the South African Plateau (Said et al, 2015). Two main periods of uplift were documented during the thermal subsidence stage of the Agulhas Margin: (i) a 92-Ma short-lived margin-scale uplift, followed by a second one at 76 Ma located along the Outeniqua Basin, and; (ii) a long-lasting uplift from 40 to 15 Ma limited to the Durban (Thekwini) Basin (Baby et al, 2018 (Delaunay, 2018).…”
Section: Volcanic Phasesmentioning
confidence: 99%
“…These were initiated at ~23 Ma, most likely due to an uplift event of the North-eastern part of the South African Plateau (Said et al, 2015). Two main periods of uplift were documented during the thermal subsidence stage of the Agulhas Margin: (i) a 92-Ma short-lived margin-scale uplift, followed by a second one at 76 Ma located along the Outeniqua Basin, and; (ii) a long-lasting uplift from 40 to 15 Ma limited to the Durban (Thekwini) Basin (Baby et al, 2018 (Delaunay, 2018).…”
Section: Volcanic Phasesmentioning
confidence: 99%
“…Over the last two decades, high‐resolution seismic data and thermochronology data have improved our understanding of the tectonic and geomorphic evolution of Southern Africa (Baby et al, ; Baby et al, ; Brown et al, ; Guillocheau et al, ; Said et al, ; Stanley et al, ; Tinker et al, ). For example, Hu et al () recently proposed a lithospheric delamination model for the uplift history of southern Africa based on seismic observations and geodynamic modeling.…”
Section: Application To Southern Africamentioning
confidence: 99%
“…However, the Late Cretaceous is a period of extremely long wavelength (several thousands of kilometres km) lithosphere deformation that is influenced by mantle dynamics (e.g. Nyblade and Robinson, 1994;Gurnis et al, 2000;De Wit,2007) • S7 sequence boundary (around the Cretaceous-Paleogene boundary, 67.3-63.2 Ma) is a regional-scale unconformity that extends throughout southern Africa and has a tectonic origin linked to the growth of the South African Plateau (Baby et al, 2018). However, its deformation processes are insufficiently understood.…”
Section: Discussionmentioning
confidence: 99%
“…catchment to explain the siliciclastic supply and thus the formation of the modern Zambezi Delta.• S4 sequence boundary (late Chattian, 25-23 Ma) is related to the 26 Ma unconformity thatBaby et al (2018) identified in the Durban Basin and interpreted as the paroxysmal period of the second phase of the South African Plateau uplift. This indicates a major reorganisation of drainage in the Malawi that likely extended far north before this event.…”
mentioning
confidence: 99%